A method for the preparation of a material for the removal of NAPL phase contamination

By preparing SiO2@P25 core-shell particles and loading them onto the surface of a sponge, combined with stearic acid treatment, the problems of high efficiency, economy, and environmental protection in the treatment of petroleum pollution in existing technologies have been solved, achieving high efficiency, durability, and low cost in oil-water separation.

CN118847064BActive Publication Date: 2026-11-06TIANJIN POLYTECHNIC UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410918512.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2026-11-06
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

Existing technologies for treating oil pollution suffer from problems such as secondary pollution, low separation efficiency, high energy consumption, high cost, and cumbersome operation. Furthermore, traditional sponge materials cannot be used effectively for long periods of time in oil-water separation.

Method used

SiO2@P25 core-shell particles were prepared by sol-gel method and loaded onto the surface of melamine sponge by impregnation method. Stearic acid was used to adjust the surface chemical energy to prepare SA@SiO2@P25@MS material. The material was then rolled into a porous hollow support tube to form a NAPL phase pollution removal material.

Benefits of technology

It achieves low-cost, environmentally friendly, and efficient oil-water separation. The material exhibits excellent hydrophobicity and oil absorption under harsh environments, enabling continuous and rapid separation of oil-water mixtures, and has good durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847064B_ABST
    Figure CN118847064B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing materials for removing NAPL phase contaminants, comprising the following steps: 1) A small amount of titanium dioxide P25 and ammonia water are poured into a mixed solution of ethanol and water, then tetraethyl orthosilicate is added, the mixture is stirred for 2 hours and centrifuged, and the resulting powdered precipitate is calcined at a certain temperature to obtain SiO2@P25 core-shell nanoparticles; 2) The SiO2@P25 core-shell nanoparticles are added to a mixed solution of polyvinyl butyral and anhydrous ethanol; after ultrasonication and stirring for 2 hours, melamine sponge is added... SiO2@P25@MS is obtained by immersing the sponge in a mixed solution for 60-120 seconds and drying it at a certain temperature. The immersion-drying process can be repeated 5-8 times to obtain a sample. 3) The obtained sponge is immersed in stearic acid solution for a period of time and ultrasonically treated. After drying, SA@SiO2@P25@MS is obtained. 4) SA@SiO2@P25@MS is rolled onto a porous hollow support tube to obtain a material that can be used to remove NAPL phase contamination. This material can continuously, efficiently and quickly remove NAPL phase contamination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material manufacturing and forming, specifically a method for preparing materials for removing NAPL phase contamination. Background Technology

[0002] With rapid industrial development, pollution from oily wastewater originating from oilfield extraction, well drainage, petroleum refining, rock pores, abandoned mines, chemical plant accidents, and groundwater recharge is becoming increasingly serious. Petroleum, as a major component of global energy, plays a crucial role in economic and social development. However, improper handling or human factors during petroleum extraction, transportation, processing, and storage can lead to soil and groundwater pollution. Petroleum is a complex mixture, mainly comprising three types of compounds: saturated hydrocarbons, aromatics, and heteroatoms. Aromatics include monocyclic and polycyclic aromatic hydrocarbons (PAHs), composed of 2 to 6 aromatic rings, and are considered carcinogenic, teratogenic, and mutagenic toxic substances, and are important components of non-aqueous liquids (NAPLs). Therefore, non-aqueous liquids (NAPLs) are prevalent in oil-contaminated groundwater, primarily originating from oil and gas exploration, extraction, transportation, drilling platforms, and related chemical industrial production such as refining, seriously endangering aquatic life and human health. Light non-aqueous phase liquids (LNAPLs) have a large diffusion area and thin thickness, while heavy non-aqueous phase liquids (DNAPLs) continuously dissolve into groundwater, leading to long-term substandard groundwater quality. In recent years, oil-water separation involving NAPL phases has attracted the attention of many companies and researchers, resulting in the development of several technologies to remediate petroleum NAPL-contaminated sites, achieving significant progress. These technologies mainly include excavation and replacement, centrifugation, flocculation, adsorption, catalysis, oxidation (persulfate, permanganate, hydrogen peroxide, ozone), bioremediation, and multiphase extraction. However, these methods often suffer from secondary pollution, low separation efficiency, high energy consumption, high cost, and cumbersome operation and maintenance. To address these issues, developing green, efficient, and economical separation technologies is an urgent priority for both industry and academia. Superwetting porous adsorbent materials exhibit excellent oil-water selective adsorption performance, making them one of the ideal solutions for achieving efficient, convenient, and green oil-water separation.

[0003] Sponges, as three-dimensional organic adsorbent materials, have attracted much attention due to their excellent mechanical properties, high porosity, and good adsorption capacity. Currently, research focuses on commercial polymer sponge materials such as polyurethane and melamine, aiming to achieve a transformation from hydrophilic to superhydrophobic through surface modification. Superhydrophobic modification significantly improves the oil absorption capacity of sponges. To further enhance oil absorption, researchers modify sponges with nanoparticles and organic compounds, incorporating them into the sponge framework to modify its surface area. Using nanoparticles in material composite preparation allows for high control over scaling and enhanced performance. In addition, low surface energy materials can be used to modify the sponge surface to improve hydrophobicity. Commonly used low surface energy materials include silane coupling agents, polydimethylsiloxane (PDMS), polytetrafluoroethylene (PTFE), and perfluoroethylene propylene (FEP). Yang Zhuohong et al. used melamine sponge as a base and oxidatively polymerized it with dopamine. They modified the polydopamine melamine sponge with metallic nickel and used polydimethylsiloxane and curing agent to hydrophobically modify the sponge for oil-water separation. The patent number is CN202211270739.5. Zhang et al. used a mixture of graphene oxide (GO) and polytetrafluoroethylene (PTFE) to modify the surface of melamine sponge (MS). The water contact angle reached 168°, and a superhydrophobic material was successfully prepared. The technology was published in the Journal of Inorganic Materials, 2020, Vol. 35, No. 4, pp. 475-481. The article title is: Preparation of superhydrophobic composite sponge and its application in oil-water separation[J]. Journal of Inorganic Materials, 2020, 35(4): 475-481. The sponges prepared by the above methods cannot separate oil-water mixtures for a long time, and need to be treated after adsorption saturation before reuse. Chinese patent ZL2015108075725 discloses an "enhanced oil-absorbing film material, component and preparation method thereof", which proposes to use graphene, polyvinylidene fluoride, pore-forming agent and other materials to modify the surface of porous polymer material and cover it on the surface of porous tube support material to make a membrane component. After providing negative pressure at one end, it can be used to continuously separate oil-water mixtures. However, it is expensive and contains stable fluorocarbon CF2 structure, which causes PFAS pollution, which is contrary to the concept of "green development".

[0004] Stearic acid, also known as octadecanoic acid, is a widely distributed fatty acid found in many animal and vegetable oils. Loading it onto a substrate surface can significantly reduce its surface energy, thus achieving a hydrophobic effect. Due to its good biocompatibility, excellent hydrophobic properties, low cost, environmental friendliness, and stable performance, it has become a popular material for hydrophobic modification. Wei Yixin et al. prepared a hydrophobic and oleophilic adsorbent material by modifying melamine sponge with a titanium dioxide / graphene oxide / stearic acid composite (patent number CN202010069604.7). Jiang et al. dispersed expanded graphite (EG), stearic acid, and Fe3O4 magnetic nanoparticles on the surface of a polyurethane (PU) sponge framework to prepare a magnetic hydrophobic composite polyurethane sponge for oil-water separation, achieving an oil absorption capacity of 32-40 g·g. -1 Moreover, it has magnetic responsiveness. The technology was disclosed in the Journal of Applied Sciences, 2010, Vol. 10, No. 4, p. 1453, titled: Magnetic and hydrophobic composite polyurethane sponge for oil-water separation, namely Jiang P, Li K, Chen X, et al. Magnetic and hydrophobic composite polyurethane sponge for oil-water separation[J]. Applied Sciences, 2020, 10(4): 1453.

[0005] In summary, the development of a fluorine-free, biocompatible, efficient, and durable material is a key theme for the sustainable development of oil-water separation applications and a critical requirement for NAPL (Non-Acid-Based Liquid) treatment. However, developing low-cost and environmentally friendly multifunctional superhydrophobic materials presents considerable challenges. This research offers a novel and meaningful approach for the continuous and efficient treatment of NAPL phase contamination. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the technical problem this invention aims to solve is to provide a method for preparing materials for removing NAPL phase contaminants.

[0007] Therefore, the technical solution of the present invention is as follows:

[0008] A method for preparing a NAPL phase contaminant removal material includes the following steps:

[0009] (1) Preparation of SiO2@P25 core-shell particles: A small amount of titanium dioxide P25 and ammonia water were poured into a mixed solution of ethanol and water, and then tetraethyl orthosilicate was added. After stirring and reacting for 2 hours, the mixture was centrifuged. The resulting powder precipitate was calcined at a certain temperature to obtain SiO2@P25 silicon dioxide titanium dioxide core-shell nanoparticles.

[0010] (2) Preparation of SiO2@P25@MS: SiO2@P25 core-shell nanoparticles were added to a mixed solution of polyvinyl butyral and anhydrous ethanol; after sonication and stirring for 2 hours, melamine sponge was immersed in the mixed solution for 60-120 seconds, and finally dried at a certain temperature to obtain SiO2@P25@MS. The immersion-drying process can be repeated 5-8 times to obtain samples.

[0011] (3) The dried sponge was immersed in stearic acid solution for a period of time and ultrasonically treated, and then dried to obtain SA@SiO2@P25@MS;

[0012] (4) The SA@SiO2@P25@MS obtained in step 3 is rolled onto a porous hollow support tube and one end is closed to obtain a material that can be used for NAPL phase contamination removal.

[0013] Preferably, the titanium dioxide P25 has a particle size of <50nm; the mass ratio of titanium dioxide P25, ammonia, and tetraethyl orthosilicate is 3:10:1.

[0014] Preferably, the ethanol content in the ethanol and water mixture in step (1) is 20 wt%.

[0015] Preferably, the porous hollow support tube in step (4) is made of polyvinyl chloride or stainless steel.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] (1) This invention prepares SiO2@P25 core-shell particles by sol-gel method, and then loads them onto the surface of melamine sponge as a substrate by impregnation. SA@SiO2@P25@MS is prepared by adjusting the surface chemical energy with stearic acid while retaining its original porous structure. The surface morphology, wettability, adsorption capacity and corrosion resistance are tested and characterized by scanning electron microscopy and contact angle test. SA@SiO2@P25@MS has the characteristics of nanoscale roughness and low chemical energy. The substrate and nanoparticle functional layer have good bonding performance. The prepared SA@SiO2@P25@MS has good hydrophobicity, excellent oil absorption and acid / alkali resistance. The overall method is simple and environmentally friendly, and is suitable for oil-water separation process in harsh environments.

[0018] (2) This method is low in cost, simple in process, and environmentally friendly. After being rolled into a porous hollow support tube, the resulting NAPL phase pollution removal material can continuously, efficiently and quickly separate oil-water mixtures without excavation, and has obvious gain effect. Attached Figure Description

[0019] Figure 1This is a scanning electron microscope image of the SA@SiO2@P25@MS material prepared in Example 1 of this invention;

[0020] Figure 2 Optical photographs showing the wettability of the SA@SiO2@P25@MS material prepared in Example 1 of this invention to tea, milk, water, dye aqueous solution, beverages, kerosene, and diesel oil.

[0021] Figure 3 The figures show the water contact angle of the SA@SiO2@P25@MS material prepared in Example 1 of this invention and the result after 50 extrusion cycle adsorption tests.

[0022] Figure 4 The image shows the water contact angle of the SA@SiO2@P25@MS material prepared in Example 1 of this invention after soaking at different pH values ​​for 24 hours.

[0023] Figure 5 The adsorption capacity of the SA@SiO2@P25@MS material prepared in Example 4 of this invention for different organic solvents and oils;

[0024] Figure 6 The separation efficiency, throughput, and recycling performance of the NAPL phase contaminant removal material finally obtained in Example 4 of this invention for oil-water mixtures are shown. Detailed Implementation

[0025] To make the technical problems, technical solutions and beneficial effects of the present invention clearer, embodiments of the present invention are given below. The specific embodiments are only used to further describe the preparation, performance and application of NAPL phase pollution removal materials.

[0026] Example 1

[0027] (1) Cleaning of melamine sponge: Cut melamine sponge with a thickness of 0.2cm into 10cm×25cm size, soak it in 60° ethanol solution for 1h and then dry it. Finally, ultrasonically clean the sponge in pure water for 30min and then dry it in a 60° vacuum oven.

[0028] (2) Preparation of SiO2@P25 core-shell particles: 1g of P25 and 5mL of ammonia water were added to 75mL of 20wt% ethanol aqueous solution. After stirring at 60° for 0.5h, 0.5mL of tetraethyl orthosilicate was added. The reaction temperature was maintained and stirred for 2h. The above solution was washed and centrifuged 3 times respectively. The solution was calcined at 300° in a muffle furnace and then ground to obtain SiO2@P25 core-shell particles.

[0029] (3) Preparation of SiO2@P25@MS: 1g PVB was added to 500mL of anhydrous ethanol solution and stirred at room temperature until dissolved. Then 2.5g SiO2@P25 particles were added, sonicated for 0.5h and stirred for 2h. The pretreated melamine sponge was immersed in SiO2@P25 ethanol solution and sonicated for 1min. After being taken out, it was placed in an oven at 60℃ and dried. The above immersion-drying steps were repeated 6 times.

[0030] (4) Preparation of SA@SiO2@P25@MS: 2.5g of stearic acid was added to 250mL of anhydrous ethanol and stirred at 55° for 2h. The SiO2@P25@MS that had been impregnated 6 times was then impregnated in the stearic acid solution for 180s. After being removed, it was placed in an oven at 60° for 4h to dry, thus obtaining SA@SiO2@P25@MS.

[0031] (5) The SA@SiO2@P25@MS obtained in step 4 is pressed and rolled into a stainless steel porous hollow support tube to obtain a material that can be used for NAPL phase pollution removal.

[0032] The SA@SiO2@P25@MS prepared in this embodiment (cut into 2×2×0.2cm pieces) 3 The material exhibits a spherical water droplet shape on its surface, with a water contact angle of 153°, meeting the superhydrophobic standard. Even after 50 compression adsorption tests, the contact angle remains at 145°. The adsorption capacities for common NAPL phase liquids—kerosene, carbon tetrachloride, xylene, dichloromethane, pump oil, engine oil, n-hexane, soybean oil, and diesel—are 89.6, 138.3, 85.7, 96.8, 63.7, 69.8, 57.6, 98.2, and 64.3 g·g⁻¹, respectively. Furthermore, after immersion in hydrochloric acid / sodium hydroxide solutions with pH values ​​of 3, 5, 7, 9, 11, and 13 for 24 hours, it still retains strong hydrophobicity, indicating excellent corrosion resistance. The NAPL phase contaminant removal material finally obtained in this embodiment is sealed at one end with AB glue and placed vertically in an oil-water mixture. The other end is connected to a vacuum pump through a pipeline to apply negative pressure (-5 kPa). It can effectively separate kerosene and water mixtures (250 mL each of kerosene and water). By observing the oil in the collection bottle, no visible water was found. After 25 consecutive separations, the separation efficiency still reached 97% (collected oil volume - water volume in oil / initial added oil volume × 100%), showing good durability. At the same time, its oil flux (tested by immersing it in kerosene, collected oil volume / working area × working time) can reach a maximum of 16370.13 Lm. -2 ·h -1 .

[0033] Example 2

[0034] (1) Cleaning of melamine sponge: Cut melamine sponge with a thickness of 0.2cm into 10cm×25cm size, soak it in 60° ethanol solution for 1h and then dry it. Finally, ultrasonically clean the sponge in pure water for 30min and then dry it in a 60° vacuum oven.

[0035] (2) Preparation of SiO2@P25 core-shell particles: 1g of P25 and 5mL of ammonia water were added to 75mL of 25wt% ethanol aqueous solution. After stirring at 60° for 0.5h, 0.5mL of tetraethyl orthosilicate was added. The reaction temperature was maintained and stirred for 2h. The above solution was washed and centrifuged 3 times respectively. The solution was calcined at 300° in a muffle furnace and then ground to obtain SiO2@P25 core-shell particles.

[0036] (3) Preparation of SiO2@P25@MS: 1.5g PVB was added to 500mL of anhydrous ethanol solution and stirred at room temperature until dissolved. Then, 2.5g SiO2@P25 particles were added, and the mixture was sonicated for 0.5h and stirred for 2h. The pretreated melamine sponge was then immersed in SiO2@P25 ethanol solution and sonicated for 5min. After removal, it was placed in an oven at 60℃ and dried. The above immersion-drying steps were repeated 5 times.

[0037] (4) Preparation of SA@SiO2@P25@MS: 2.5g of stearic acid was added to 250mL of anhydrous ethanol and stirred at 55° for 2h. The SiO2@P25@MS that had been impregnated 5 times was impregnated in the stearic acid solution for 200s, taken out, and dried in an oven at 60° for 4h to obtain SA@SiO2@P25@MS.

[0038] (5) The SA@SiO2@P25@MS obtained in step 4 is pressed and rolled into a stainless steel porous hollow support tube to obtain a material that can be used for NAPL phase pollution removal.

[0039] Testing showed that the SA@SiO2@P25@MS obtained by immersion in kerosene five times in this embodiment had a contact angle of 131.4° with water droplets and an adsorption capacity of 33.5 times its own weight for kerosene. The NAPL phase contaminant removal material finally prepared in this embodiment, with one end sealed with AB glue and placed vertically in an oil-water mixture, and the other end connected to a vacuum pump under negative pressure (-5 kPa), effectively separated kerosene and water mixtures (250 mL each). No visible water was observed in the oil collected in the collection bottle. After 25 consecutive separations, the separation efficiency still reached 92% (collected oil volume - water volume in oil / initial added oil volume × 100%), exhibiting good durability. Simultaneously, its oil flux (tested by immersion in kerosene, collected oil volume / working area × working time) reached a maximum of 23951.89 L·m⁻¹. -2 ·h -1 .

[0040] Example 3

[0041] (1) Cleaning of melamine sponge: Cut melamine sponge with a thickness of 0.2cm into 10cm×25cm size, soak it in 60° ethanol solution for 1h and then dry it. Finally, ultrasonically clean the sponge in pure water for 30min and then dry it in a 60° vacuum oven.

[0042] (2) Preparation of SiO2@P25 core-shell particles: 1g of P25 and 5mL of ammonia water were added to 75mL of 20wt% ethanol aqueous solution. After stirring at 60° for 0.5h, 0.5mL of tetraethyl orthosilicate was added. The reaction temperature was maintained and stirred for 2h. The above solution was washed and centrifuged 3 times respectively. The solution was calcined at 300° in a muffle furnace and then ground to obtain SiO2@P25 core-shell particles.

[0043] (3) Preparation of SiO2@P25@MS: 1g PVB was added to 500mL of anhydrous ethanol solution and stirred at room temperature until dissolved. Then 2.5g SiO2@P25 particles were added, sonicated for 0.5h and stirred for 2h. The pretreated melamine sponge was immersed in SiO2@P25 ethanol solution and sonicated for 5min. After being taken out, it was placed in an oven at 60℃ and dried. The above immersion-drying steps were repeated 7 times.

[0044] (4) Preparation of SA@SiO2@P25@MS: 2.5g of stearic acid was added to 250mL of anhydrous ethanol and stirred at 55° for 2h. The SiO2@P25@MS that had been impregnated 5 times was impregnated in the stearic acid solution for 180s, taken out, and dried in an oven at 60° for 4h to obtain SA@SiO2@P25@MS.

[0045] (5) The SA@SiO2@P25@MS obtained in step 4 is pressed and rolled into a porous hollow support tube made of polyvinyl chloride to obtain a material that can be used for NAPL phase pollution removal.

[0046] Testing showed that the SA@SiO2@P25@MS obtained in this embodiment had a contact angle of 145.4° for water droplets and an adsorption capacity of 57.3 g·g for kerosene. -1 The NAPL phase contamination removal material finally obtained in this embodiment is sealed at one end with AB glue and placed vertically in an oil-water mixture. The other end is connected to a vacuum pump through a pipeline to apply negative pressure (-5 kPa). It can effectively separate kerosene and water mixtures (250 mL each of kerosene and water). By observing the oil in the collection bottle, no visible water was found. After 25 consecutive separations, the separation efficiency can still reach 97% (collected oil volume - water volume in oil / initial added oil volume × 100%), which has good durability.

[0047] Example 4

[0048] (1) Cleaning of melamine sponge: Cut melamine sponge with a thickness of 0.2cm into 10cm×25cm size, soak it in 60° ethanol solution for 1h and then dry it. Finally, ultrasonically clean the sponge in pure water for 30min and then dry it in a 60° vacuum oven.

[0049] (2) Preparation of SiO2@P25 core-shell particles: 1g of P25 and 5mL of ammonia water were added to 75mL of 20wt% ethanol aqueous solution. After stirring at 60° for 0.5h, 0.5mL of tetraethyl orthosilicate was added. The reaction temperature was maintained and stirred for 2h. The above solution was washed and centrifuged 3 times respectively. The solution was calcined at 300° in a muffle furnace and then ground to obtain SiO2@P25 core-shell particles.

[0050] (3) Preparation of SiO2@P25@MS: 1g PVB was added to 500mL of anhydrous ethanol solution and stirred at room temperature until dissolved. 2.5g SiO2@P25 particles were added, and the mixture was sonicated for 0.5h and stirred for 2h. The pretreated melamine sponge was then immersed in SiO2@P25 ethanol solution and sonicated for 1min. After being removed, it was placed in an oven at 60℃ and dried. The above immersion-drying steps were repeated 8 times.

[0051] (4) Preparation of SA@SiO2@P25@MS: 2.5g of stearic acid was added to 250mL of anhydrous ethanol and stirred at 55° for 2h. The SiO2@P25@MS that had been impregnated 8 times was impregnated in the stearic acid solution for 200s, taken out, and dried in an oven at 60° for 4h to obtain SA@SiO2@P25@MS.

[0052] (5) The SA@SiO2@P25@MS obtained in step 4 is pressed and rolled into a stainless steel porous hollow support tube to obtain a material that can be used for NAPL phase pollution removal.

[0053] Testing showed that the SA@SiO2@P25@MS obtained in this embodiment had a contact angle of 150.4° for water droplets and an adsorption capacity of 71.5 g·g for kerosene. -1 The NAPL phase contamination removal material finally obtained in this embodiment is sealed at one end with AB glue and placed vertically in an oil-water mixture. The other end is connected to a vacuum pump through a pipeline to apply negative pressure (-5 kPa). It can effectively separate kerosene and water mixtures (250 mL each of kerosene and water). By observing the oil in the collection bottle, no visible water was found. After 25 consecutive separations, the separation efficiency can still reach 98% (collected oil volume - water volume in oil / initial added oil volume × 100%), which has good durability.

Claims

1. A method for preparing a material for removing NAPL phase contaminants, characterized in that, The method includes the following steps: (1) Preparation of SiO2@P25 core-shell particles: A small amount of titanium dioxide P25 and ammonia water were poured into a mixed solution of ethanol and water, and then tetraethyl orthosilicate was added. After stirring and reacting for 2 hours, the mixture was centrifuged. The resulting powder precipitate was calcined at a certain temperature to obtain SiO2@P25 silicon dioxide titanium dioxide core-shell nanoparticles. (2) Preparation of SiO2@P25@MS: SiO2@P25 core-shell nanoparticles were added to a mixed solution of polyvinyl butyral and anhydrous ethanol; after sonication and stirring for 2 hours, melamine sponge was immersed in the mixed solution for 60-120 seconds, and finally dried at a certain temperature to obtain SiO2@P25@MS. The immersion-drying process can be repeated 5-8 times to obtain samples. (3) The dried sponge was immersed in anhydrous ethanol solution of stearic acid for a period of time and ultrasonically treated. After drying, SA@SiO2@P25@MS was obtained. (4) The SA@SiO2@P25@MS obtained in step 3 is rolled onto a porous hollow support tube and one end is closed to obtain a material that can be used for NAPL phase contamination removal.

2. The preparation method according to claim 1, characterized in that, The titanium dioxide P25 in step (1) has a particle size of no more than 50 nm; the volume ratio of titanium dioxide P25, ammonia, and tetraethyl orthosilicate is (2-4):10:1; the mass percentage of ethanol in the ethanol and water mixture in step (1) is 20-30 wt%, and the volume of the mixture is 10-15 times that of ammonia; the calcination temperature in step (1) is 300℃, and the sintering time is 140-180 min.

3. The preparation method according to claim 1, characterized in that, In step (2), the mass fraction of polyvinyl butyral in the mixed solution of polyvinyl butyral and anhydrous ethanol is 0.1-0.5 wt%; in step (2), the mass fraction of SiO2@P25 core-shell nanoparticles in the mixed solution of polyvinyl butyral and anhydrous ethanol is 0.5-1 wt%; and in step (2), the drying temperature is 60-65℃.

4. The preparation method according to claim 1, characterized in that, The stearic acid solution in step (3) is an ethanol solution of stearic acid, wherein the mass ratio of stearic acid to ethanol is (1-5):100, and the immersion time is 170-200s; the drying temperature in step (3) is set to 55-70℃.

5. The preparation method according to claim 1, characterized in that, The porous hollow support tube in step (4) can be made of one of the following materials: polyvinyl chloride, polypropylene, polyethylene, polyimide, or stainless steel.

Citation Information

Patent Citations

  • Magnetic super-hydrophobic oleophylic sponge with photothermal effect as well as preparation method and application of magnetic super-hydrophobic oleophylic sponge

    CN115895024A

  • Melamine sponge with nanoparticles loaded on surface, and preparation method and application thereof

    CN109535475A

  • Preparation method of titanium dioxide / graphene oxide / stearic acid composite modified sponge

    CN111250061A